Strategi Penanaman Nilai Sila Ke-2 Pancasila Pada Masa Pandemi Covid-19, Oleh Mahasiswa Universitas Pembangunan Nasional Veteran Jakarta - Setiyawati, Marina Ery; Subakdi, Subakdi; Hermina, Hermina; Wahyuningtyas, Widayani (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This study aims to describe the cultivation of the values of just and cultured humanity to UPNVJ students.Pancasila values are the foundational principles or perspectives in actions, even during the Covid-19 pandemic,these values must be upheld, especially in implementing government policies in the field of education. Lecturers,as essential components of the educational workforce, have the task of facilitating the learning process. Cultivationstrategies refer to the methods and art of utilizing resources to achieve specific goals. Planting the values ofPancasila's second principle in higher education needs to be applied to confront the era of globalization, whichwitnesses the influx of various new cultures and civilizations from different nations around the world. Theimplementation of humanitarian values in national and societal life certainly cannot escape violations related tothese values. This study employs a quantitative research approach. The subjects of this study are students of theNational Veteran Development University Jakarta. Data collection is carried out by distributing questionnaires tothe students. The results of this study can be concluded that the cultivation of the values of just and culturedhumanity by UPNVJ students predominantly yields highly agreeable results. It is expected that students can instillthe values of the second principle of Pancasila, which is the value of just and cultured humanity, in their dailylives.